Tunnel lining design guide (Thomas Telford, 2004)
This is a reference to the recommended standards and rules applicable to formulation for bored tunnels and shafts in any type of ground condition. It is also a useful resource for those involved in the procurement, operation or maintenance of tunnels, or those seeking to acquire data for use in production.